Students’ Reading Anxiety and Comprehension in An Indonesian Madrasah: A Correlational Case Study - Nuri Oktaviani Sakinah; Hasan Basri (Institut Agama Islam Negeri Madura, 2025)
The capacity to extract information from written texts and exhibit knowledge or comprehension of that information is known as reading comprehension. The word